Pengaruh Gaya Kepemimpinan, Disiplin Kerja Motivasi, dan Insentif Karyawanterhadap Kinerja Karyawan di PT. Inti Sukses Garmindo Kab. Semarang - Teti Safari; Chusnul Chomaydah; Endro Pramono (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
The purpose of this research is to determine and analyze the influence of leadership style on employee performance. Know and analyze work discipline on employee performance. Knowing and analyzing motivation for employee performance. Knowing and analyzing employee incentives on employee performance. The population in this study were all cutting employees of PT. Garmindo District Success Core. Semarang. The research was carried out by sampling, using probability sampling techniques, obtaining a sample of 92 respondents. The analysis technique used is multiple linear regression. The research results can be concluded that: Leadership style has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Employee incentives have a positive and significant effect on employee performance. Leadership style, work discipline, motivation and employee incentives together have a positive and significant effect on employee performance.